Antiproliferative activity of a new xanthone derivative from leaves of Garcinia nobilis Engl. Issue 24 (17th December 2021) - Fouotsa, Hugues; Dzoyem, Jean Paul; Lannang, Alain Meli; Stammler, Hans-Georg; Mbazoa, Celine Djama; Luhmer, Michel; Nkengfack, Augustin Ephrem; Allémann, Éric; Delie, Florence; Meyer, Franck; Sewald, Norbert
Abstract: A new xanthone, mboudiexanthone (1 ), together with five known compounds, euxanthone (2 ), isogarcinol (3 ), garcinol (4 ), betulinic acid (5 ) and zeorin (6 ) were isolated from the leaves of Garcinia nobilis Engl. The structures were determined by 1D and 2D NMR techniques and X-ray diffraction for 6 . The in vitro antiproliferative properties of isolated compounds were evaluated against the human breast cancer cell line MCF-7. All compounds showed an antiproliferative activity with an IC50 value down to ∼11 µM for isogarcinol. Abstract : UF0001